PENYULUHAN KEPADA MASYARAKAT WARGA BINAAN LAPAS BARELANG BATAM MENGAMPUNI - Simamora, Helprida; Rejeki Bangun; Sihombing, Jonmaianto; Yopi (JUPADAI : Jurnal Pengabdian Kepada Masyarakat, 2024)
Correctional institutions are tasked with providing guidance to inmates according to the specified system and are part of the guidance in the final stages (Law No. 12., Year 1995 article 1 verse 1). WBP are residents who are undergoing guidance for a certain period of time to be prepared to enter society according to the court's decision. In the prison, WBP need vocational skills training or spiritual guidance (religious, mental and behavioral) so that preparation to enter society is truly accepted. With various backgrounds experienced, WBP have a variety of personalities both before and after entering the prison. This inner situation greatly influences the metamorphosis of the personality that exists in him after returning to his family/society after undergoing guidance in the prison. Efforts to provide insight as believers, it is necessary to abandon old ways of life (which are the cause of 'entry' into the prison) with various types of crimes that cause sin. Therefore, WBP needs to be given spiritual education for a better life in the present and future by Forgiving, both forgiving themselves for mistakes they have made in the past and forgiving others who make them angry so that they fall into sin. The attitude of forgiving others is not easy, because of various factors that exist within a person. This counseling and community service is carried out to provide spiritual education for WBP of Barelang Batam Penitentiary for gradual changes in attitude and physical during their community service so that when they leave the penitentiary they will have a better personality, be faithful and practice it in the community. This counseling is very important for the change of WBP because support from outside the penitentiary really helps them to be mentally strong, be able to accept situations, reduce stress and various other situations and it is hoped that in the future they can also provide the knowledge they gained while in the penitentiary to other communities so that they do not experience what they have experienced.